SUSPENTION OF CUSTOMS CLEARANCE OF GOODS OR ITEMS HAVING INTELLECTUAL PROPERTY OBJECTS AS A WAY OF SECURING FOR A CLAIM - Хамзін, Тимур Рафаїлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the concept of ensuring the claim is analyzed, types of claim protection in the GPC and the CPC of Ukraine are given. The role of the Institute to secure the claim during implementation by income and fees mechanism to protect intellectual property rights when moving goods containing intellectual property across the customs border of Ukraine. Done generalization of judicial practice of commercial courts to secure claims in cases of intellectual property rights when stopped by customs clearance agency revenues and fees. Provided assessment of changes to the EPC and the CPC of Ukraine on the introduction of this type of the claim, as the suspension of customs clearance or objects. Methods: using general method allowed to concentrate knowledge accumulated scientific knowledge and practice of law in general and the suspension of clearance items at customs Results: are determined preconditions low efficiency of modern customs. Discussion: problems of legal provision of customs clearance of objects of intellectual property.